In-vitro Studies on the Cultural Characteristics of Selected Ectomycorrhizal Fungi - Radhakrishnan, Ayswarya; Mohan, V. (Indian Forester, 2008)
The mycorrhizal symbiosis between plants and fungi is essential for the survival of both partners and it has been suggested that this symbiosis was a prerequisite for the successful colonization by the plants. Among the different mycorrhizal fungi, the ectomycorrhizal fungi are mostly associated with the tree crops particularly conifers and certain angiosperms. Unlike AM fungi, the ectomycorrhizal fungi can be pure cultured and mass produced in synthetic media under laboratory conditions. In the present study an attempt was made to identify the most suitable culture medium for the better growth of three different ectomycorrhizal fungal isolates viz., Pisolithus albus. It was found that all the three isolates performed well in MMN and PHA media. Another study was conducted wherein the three different ectomycorrhizal fungi viz., Laccaria fraterna, Scleroderma sp. and Pisolithus albus were grown in MMN media maintained at seven different pH levels. It was observed that the MMN liquid medium at moderate pH level (5.5 and 6.0) was found suitable for the better growth of all the fungi and significance of the findings is discussed.